PENGARUH DRYING AND WETTING CYCLE TERHADAP KUAT GESER TANAH ALAHAN PANJANG SUMATERA BARAT - Ramadhan, Wira Anugerah; Andayono, Totoh (Teknik Sipil Universitas Negeri Padang, 2023)
The purpose of this study was to determine how much influence the drying and wetting cycle had on the shear strength of the soil in Alahan Panjang, West Sumatra. The location of the soil sampling is on the slopes of Alahan Panjang, West Sumatra with coordinates 1º03’44.24ʹʹS and 100º45ʹ37.00ʹʹ E. Soil sampling was carried out by disturbed and undisturbed methods.In this study, there were two tests carried out, namely the physical and mechanical properties of the soil. The results showed that based on USCS and AASHTO and the Gs specific gravity test, this soil sample was classified as non-organic clay with high plasticity. The effect of drying and wetting cycle makes the shear strength of the soil to be small or reduced.The highest shear strength is obtained when the optimum water content is 0.4504 Kg/cm2.At the time of reducing the moisture content or drying process from the optimum moisture content of 10% and 20%, the yield of the soil shear strength decreased by 0.4173 Kg/cm2 and 0.3466 Kg/cm2, respectively.Meanwhile, when the water content was added from the optimum moisture content or wetting process by 10% and 20%, the shear strength also decreased, respectively, namely 0.3349 Kg/cm2 and 0.2835 Kg/cm2.